GLOBECOM 2020 - 2020 IEEE Global Communications Conference 2020
DOI: 10.1109/globecom42002.2020.9348209
|View full text |Cite
|
Sign up to set email alerts
|

On the Interference Immunity of Visible Light Communication (VLC)

Abstract: Visible Light Communication (VLC) relies on the dual use of existing light infrastructure for wirelessly send data. VLC is regarded as a "green", cost-effective and secure communication technology. Moreover, VLC has been always considered immune to Radio Frequency (RF) waves. The only type of interference that has always been included in the channel model is the optical interference. Nevertheless, all the interference components potentially impacting on the performance of the system should be integrated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In contrast, VLC offers several key advantages: Spectrum availability: VLC, categorized under free-space optical communication, provides an expansive spectrum, offering substantially larger bandwidth than the RF spectrum utilized by conventional wireless technologies [ 40 ]; Resistance to RF interference and overcrowding: VLC is immune to electromagnetic interference that can disturb sensitive electronic systems. This unique property enables VLC to function even in environments where RF usage is restricted, such as hospitals, airplanes, power plants, and sensitive industrial settings [ 41 ]; Cost-effective implementation: VLC leverages readily available, cost-effective LEDs. Existing infrastructures can be conveniently adapted for VLC by incorporating LEDs into the existing lighting systems, thereby providing concurrent communication and illumination.…”
Section: The Basics Of Vlcmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, VLC offers several key advantages: Spectrum availability: VLC, categorized under free-space optical communication, provides an expansive spectrum, offering substantially larger bandwidth than the RF spectrum utilized by conventional wireless technologies [ 40 ]; Resistance to RF interference and overcrowding: VLC is immune to electromagnetic interference that can disturb sensitive electronic systems. This unique property enables VLC to function even in environments where RF usage is restricted, such as hospitals, airplanes, power plants, and sensitive industrial settings [ 41 ]; Cost-effective implementation: VLC leverages readily available, cost-effective LEDs. Existing infrastructures can be conveniently adapted for VLC by incorporating LEDs into the existing lighting systems, thereby providing concurrent communication and illumination.…”
Section: The Basics Of Vlcmentioning
confidence: 99%
“…Resistance to RF interference and overcrowding: VLC is immune to electromagnetic interference that can disturb sensitive electronic systems. This unique property enables VLC to function even in environments where RF usage is restricted, such as hospitals, airplanes, power plants, and sensitive industrial settings [ 41 ];…”
Section: The Basics Of Vlcmentioning
confidence: 99%
“…The presence of environmental source of interference (e.g., sunlight), if not properly addressed, could prevent effective working of such a kind of technology. Moreover, it has been demonstrated that VLC is not completely immune to RF interference [14] and it needs to be carefully implemented in real environments (via realistic measurements) in order to exploit all its potential.…”
Section: F Visible Light Communication (Vlc)mentioning
confidence: 99%
“…Recently, it has been demonstrated that VLC systems are prone and vulnerable to certain types of attacks. Just as an example, in [6], the authors have demonstrated that the RF immunity of VLC is not available, and RF transmissions can interfere with VLC transmissions [6]. Based on the principle "what-you-see-is-what-you-get" that is specific for VLC, eavesdroppers can quite easily retrieve light signals at different locations, due to the diffusiveness of the light.…”
Section: Introductionmentioning
confidence: 99%